Energy management of a grid-connected hydrokinetic system under Time of Use tariff - Kusakana, Kanzumba (Renewable energy, 2017)
In this work, the optimal power scheduling for a grid-connected hydrokinetic-battery hybrid system is proposed to sufficiently explore hydrokinetic energy and to benefit customers at demand side. The developed model for the hybrid system’s optimal power flow management aims to minimize electricity cost subject to the power balance, hydrokinetic and battery storage outputs as well as other operational constraints. With respect to demand side management, an optimal control method is developed to schedule the power flow of hybrid system over 24-h. Simulations are performed using MATLAB (R2016a), and the results demonstrate that operating the proposed hybrid system under the developed optimal energy management model can reduce the operation cost and allow consumers to generate substantial income by selling power to the grid. •Grid connected hydrokinetic-battery hybrid system is proposed.•TOU with power selling is modeled to minimize electricity cost.•Optimal control is developed to dispatch power flow economically.